2022
DOI: 10.3390/ijms23158560
|View full text |Cite
|
Sign up to set email alerts
|

The Treatment Efficiency and Microbiota Analysis of Sapindus mukorossi Seed Oil on the Ligature-Induced Periodontitis Rat Model

Abstract: Periodontitis is a common oral disease mainly caused by bacterial infection and inflammation of the gingiva. In the prevention or treatment of periodontitis, anti-bacterial agents are used to inhibit pathogen growth, despite increasing levels of bacterial resistance. Sapindus mukorossi Gaertn (SM) seed oil has proven anti-bacterial and anti-inflammation properties. However, the possibility of using this plant to prevent or treat periodontitis has not been reported previously. The aim of this study was to evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…The hexane and methanol extracts from SM fruit have demonstrated inhibitory effects against both S. mutans and E. faecalis [ 16 ]. The oil extracted from SM seeds exhibited inhibitory properties against periodontal pathogens and effectively mitigated the advancement of periodontitis, leading to a notable reduction in total bone loss in animal models [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The hexane and methanol extracts from SM fruit have demonstrated inhibitory effects against both S. mutans and E. faecalis [ 16 ]. The oil extracted from SM seeds exhibited inhibitory properties against periodontal pathogens and effectively mitigated the advancement of periodontitis, leading to a notable reduction in total bone loss in animal models [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chemical composition analysis revealed that S. mukorossi seed oil contains a significant amount of fatty acids, with up to 86% being unsaturated fatty acids [ 20 , 21 ]. Cell and animal studies have separately confirmed the oil’s antibacterial and anti-inflammatory effects, both in aiding skin repair [ 8 ] and stabilizing oral microbiota [ 22 ]. Interestingly, a recent study has also shown that S. mukorossi seed oil promotes osteogenic/odontogenic differentiation and matrix vesicle secretion of dental pulp stem cells [ 23 ], though the exact mechanism remains unknown.…”
Section: Introductionmentioning
confidence: 99%